Trust and Commitment:: Indicators of Successful Learning in International Joint Ventures (IJVs) - Vaidya, Sameer (Journal of Comparative International Management, 2012)
This study focused on the importance of trust and commitment to International Joint Ventures (IJVs). According to Kogut (1988), joint ventures are formed for various reasons, one of important reasons being learning between the partners. This article proposes that trust and commitment are positively related to learning between IJV partners. An empirical analysis was conducted by surveying 1000 CEOs of IJVs in India. The study does show that there is a positive relationship between learning and trust and commitment. The study also proves that IJVs with better trust mechanisms tend to learn more from their partners.